2022
DOI: 10.1029/2021gl096690
|View full text |Cite
|
Sign up to set email alerts
|

Greenland Ice Sheet Daily Surface Melt Flux Observed From Space

Abstract: Greenland Ice Sheet (GrIS) surface melt has contributed to the global sea‐level rise and the ongoing warming is expected to promote this process. This study provides a new strategy for the quantitative estimate of GrIS daily surface melt at enhanced resolution (3.125 km) from a remote sensing perspective beyond traditional regional climate models (RCMs). Daily melt flux is estimated from spaceborne radiometer observations with a back‐propagation neural network model. The network is trained with melt fluxes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…Uncertainties of the discharge estimates in this study stem from the relationship between discharge and water extent, the interpolation, the determination of the inundation period, and the effect of snow cover on the reflectance of MODIS data. Our discharge estimates failed to capture the high discharge signal in 2012 when there was an extreme melt event in the GrIS [32], [33]. Under the ultra-high discharge condition, the is almost saturated and it is not very sensitive to high flows.…”
Section: A Uncertainty Analysismentioning
confidence: 74%
“…Uncertainties of the discharge estimates in this study stem from the relationship between discharge and water extent, the interpolation, the determination of the inundation period, and the effect of snow cover on the reflectance of MODIS data. Our discharge estimates failed to capture the high discharge signal in 2012 when there was an extreme melt event in the GrIS [32], [33]. Under the ultra-high discharge condition, the is almost saturated and it is not very sensitive to high flows.…”
Section: A Uncertainty Analysismentioning
confidence: 74%
“…By applying data from three different sensors, Nghiem et al found that the melting extent in Greenland was as high as 98.6% on 12 July 2012 [10]. Zheng et al combined a combination of regional climate models, passive microwave data, and machine learning to find melting across Greenland in mid-July 2012 [38]. The extreme melting event in July 2012 may be related to anomalous warm air ridges due to high blockages in Greenland [10].…”
Section: Discussionmentioning
confidence: 99%
“…A similar (and substantially increased) network of surface-based energy balance-enabled weather stations with radiation sensors will be needed to improve model-based and satellite-based estimates of AIS surface melt and firn hydrology. A similar effort on the GrIS under the guidance of the Geological Survey of Denmark and Greenland has led to excellent ice sheet wide coverage from around 2010, enabling the calibration of satellite-based surface melt rate estimates using machine learning techniques 227 . Additional arrays of in situ observations are required to improve model representations of ice shelf flexure and hydrofracture in response to surface meltwater ponding and drainage.…”
Section: Nature Reviews Earth and Environmentmentioning
confidence: 99%